Exacerbating Staff Shortages and Student Dissatisfaction? The Impact of AACSB Accreditation on Faculty Recruitment in Australia - Margaret Lightbody (Australasian Accounting, Business and Finance Journal, 2010)
Australian accounting schools are widely perceived to be experiencing a staffing shortage. Many accounting schools are now seeking AACSB accreditation. There has been no consideration in the accounting literature of how such accreditation might impact on the future ability of accounting schools to attract the ex-practice accountants that have traditionally comprised the majority of their faculty recruits. To examine such implications, this paper presents an interpretive case study of an Australian business school which is in the process of applying for AACSB accreditation. The paper argues that an implication of the increasingly inflexible work environment driven by AACSB accreditation may be that academia becomes a less attractive workplace for ex-practitioner faculty. This may further exacerbate existing academic staff shortages and reduce diversity and professional knowledge within accounting schools, with consequent implications for teaching, student engagement, and industry engagement. This in turn may have long term ramifications for the ability of the universities to attract students and thus earn the tuition fees on which they currently rely.
Keywords: Accounting; Universities; Faculty; AACSB; Diversity; Flexible work arrangements